2012
DOI: 10.1111/j.1574-0862.2012.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Do stronger intellectual property rights promote seed exchange: evidence from U.S. seed exports?

Abstract: With increased private investment in crop breeding research in the developed world, intellectual property rights have gained importance in seed sector. Trade Related Aspects of Intellectual Property Rights (TRIPS)-plus provisions included in recent free trade agreements between the developed and developing countries show a tendency of the developed world to impose their high standards for protection of plant intellectual property on the developing world. While stronger intellectual property rights can increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…In line with these results, Eaton (2013) found no evidence that adopting plant breeders' rights benefits seed imports. Galushko (2012) has challenged this evidence concluding that stronger IPRs can foster international seed exchange.…”
Section: Iprs and Agricultural Trade: A Frame-workmentioning
confidence: 90%
See 1 more Smart Citation
“…In line with these results, Eaton (2013) found no evidence that adopting plant breeders' rights benefits seed imports. Galushko (2012) has challenged this evidence concluding that stronger IPRs can foster international seed exchange.…”
Section: Iprs and Agricultural Trade: A Frame-workmentioning
confidence: 90%
“…In the agricultural sector, the analysis must also consider some distinct features. Also, most of the empirical literature concentrates on trade flows of manufacturing products and a few empirical studies on the agricultural sector analyze the effect of IPRs on specific products, such as seeds, see for example: Yang and Woo (2006), Galushko (2012), and Eaton (2013). Considering the relevance of both trade and IPRs on the agricultural sector, our study contributes to the empirical analysis of the relation between IPRs and agricultural trade.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies of trade in manufactures have found IPRs to have a positive effect on exports, for example, Maskus and Penubarti (), Smith (), and Ivus (), while Campi and Dueñas () found that stronger IPRs have had a negative effect on trade in agricultural products. In the case of seed trade, Yang and Woo () and Eaton () both failed to detect a statistically significant effect of IPRs, while Galushko () found the positive impact of IPRs varied across different groups of crops. The current article builds on these previous studies by utilizing a larger data set and focusing on field crop seeds that include seeds susceptible to IPR infringement.…”
Section: Iprs and Tradementioning
confidence: 99%
“…In contrast, Eaton () used an index for the strength of IP protection compiled by the Economic Freedom of the World database produced by the Fraser Institute (Gwartney et al., ), although he found no statistically significant impact for this index on seed trade. Galushko () also included a dummy variable for high‐income importing countries in her sample, but in a footnote she indicates the “Rule of Law” indicator included in the World Bank's Worldwide Governance Indicators (WGI; Kauffman et al., ) was also used. Galushko () found that the latter variable was highly correlated with the dummy variable for high‐income countries, her estimation results proving robust to using either measure of property rights enforcement.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation